Highly efficient separation and enrichment of polyphenols by 6-aminopyridine-3-boronic acid-functionalized magnetic nanoparticles assisted by polyethylenimine. Issue 11 (1st March 2022) - Zhang, Yansong; Qing, Lianglei; Xu, Linna
Abstract : Synthesis routes of 6-aminopyridine-3-boronic acid-functionalized magnetic nanoparticles assisted by polyethylenimine (Fe3 O4 @PEI@PYBA). Abstract : Polyphenols have found a lot of therapeutic effects and potential applications such as antioxidant, anti-inflammatory, mutant resistance, immunosuppressant and anti-tumor properties. They can be divided into five main classes, namely flavonoids, phenolic acids, stilbenes, lignans, and others. Thus, the content detection of polyphenols in real samples such as fruit juice and tea is of great significance. Due to the presence of complex interfering components in actual samples, separation and enrichment of polyphenols prior to analysis is key. Therefore, it is quite necessary to establish a simple, low-cost and efficient purification method for cis -diol-containing polyphenols from real samples. Boronate affinity materials are able to reversibly bind cis -diol-containing compounds by forming a five- or six-membered boronic cyclic ester in aqueous media. However, conventional boronate affinity materials exhibited low binding capacity and high binding pH. In this study, the polyethyleneimine (PEI)-assisted 6-aminopyridine-3-boronic acid functionalized magnetic nanoparticles (MNPs) were developed to capture efficiently cis -diol-containing polyphenols under neutral condition. PEI was applied as a scaffold to amplify the number of boronic acid moieties. While 6-aminopyridine-3-boronic acid was used as an affinity ligand due to low p K a value and excellent water solubility toward polyphenols. The results indicated that the prepared boronic acid-functionalized MNPs provided high binding capacity and fast binding kinetics under neutral conditions. In addition, the obtained MNPs exhibited relatively high binding affinity ( K d ≈ 10 −4 M), low binding pH (pH ≥ 6.0) and tolerance of the interference of abundant sugars.